Inflation management in India. - Karia, Niki (2007)
Inflation is often described by economists as the general and persistent increase in prices across an economy. The rise in prices affects the wages, real income, production, unemployment and so on. Inflation adversely affects the growth rate in an economy and reduces savings and investments. Due to the deleterious effects it has on the economy, inflation has taken its place as a central economic issue. The point to be stressed on is that inflation is here and it is to stay, unless some effective measures can be used to control its very emergence. For more than two decades, controlling inflation has been the main goal of central banks around the world, and it has now become an issue of central and immediate importance in India. The key instrument used by Central banks in most countries is the short-term interest rate. When a country experiences persistent high inflation, interest rates are increased to bring inflation into control. However, the empirical evidence relating to the effect of interest rates on inflation is mixed and there is no evidence in the literature for India. The question is: How useful is this instrument in controlling inflation and can it be used to control inflation in India?